The Uneasy Case for Fractional- Reserve Free Banking - Hauwe, Ludwig van den Hauwe (REVISTA PROCESOS DE MERCADO, 2006)
Since a few decades several sub-disciplines within economics have witnessed a reorientation towards institutional analysis. This development has in particular also affected the fields of macroeconomics and monetary theory where it has led to several proposals for far-reaching financial and monetary reform. One of the more successful of these proposals advocates a fractional-reserve free banking system, that is, a system with no central bank, but with permission for the banks to operate with a fractional reserve. This article exposes several conceptual flaws in this proposal. In particular several claims of the fractional-reserve free bankers with respect to the purported working characteristics of this system are criticized from the perspective of economic theory. In particular, the claim that a fractional-reserve free banking system would lead to the disappearance of the business cycle is recognized as false. Furthermore an invisible-hand analysis is performed, reinforcing the conclusion that fractional-reserve free banking is incompatible with the ethical and juridical principles underlying a free society. Key words: monetary and banking regimes, comparative institutional analysis, fractional-reserve free banking, business cycle, invisible hand. Clasificación JEL: B53, E32, E42, E5, G18, H11, K39, P3, P34 Resumen: Desde hace algunas décadas varias subdisciplinas de la economía se ven reorientadas hacia el análisis institucional. Este desarrollo ha afectado más específicamente también a los campos de la macroeconomía y la teoría monetaria donde ha llevado a varias propuestas de reformas financieras y monetarias de gran alcance. Una de las propuestas más exitosas aboga por una banca libre con reserva fraccionaria, o sea un sistema sin banco central en el cual, sin embargo, los bancos puedan operar con una reserva fraccionaria. Este artículo comenta varios defectos conceptuales de dicha propuesta. Más específicamente, varias alegaciones de los banqueros de la banca libre con reserva fraccionaria relativas a las supuestas características operativas de este sistema se critican partiendo de la teoría económica. Más en particular, se denuncia como errónea la alegación de que una banca libre con reserva fraccionaria llevaría a la desaparición del ciclo económico. Además, se realiza un análisis de mano invisible lo cual refuerza la conclusión que la banca libre con reserva fraccionaria es incompatible con los principios éticos y jurídicos propios de una sociedad libre. Palabras clave: banca libre con reserva fraccionaria, ciclo económico, mano invisible.